The sociodemographic characteristics and risk factors for tuberculosis morbidity between two decades at the beginning of the 21st century at the north of Kosovo, Serbia - Smiljić, Sonja; Stanisavljević, Dejana; Radović, Blagica; Mijović, Milica; Savić, Sladjana; Ristić, Siniša; Mandić, Predrag (Vojnosanitetski pregled, 2020)
Background/Aim. Tuberculosis (TB) is a major cause of mortality and morbidity worldwide, affecting different countries disproportionally. Effective diagnosis and treatment of TB saved an estimated 43 million lives between 2000 and 2014. The aim of our study was to show socio-demographic influences, risk factors for the morbidity and clinical characteristics of tuberculosis among residents of northern Kosovo, Serbia, between two decades at the beginning of the 21st century. Methods. A prospective study was conducted at the Department for Pulmonology of the Clinical-health Centre, Kosovska Mitrovica, included all tuberculosis patients treated during two three-year periods, between 2000–2002 and 2012–2014. In total, 134 patients with tuberculosis were treated, 91 in the first observed period and 43 in the second period. Results. In both observed periods, male patients suffered from tuberculosis more frequently. In the first observed period, younger and middle age (18–49) persons suffered from tuberculosis more frequently (p = 0.014). In relation to the place of residence, in the first reporting period there were more patients from urban areas, while in the second, there were significantly more patients from rural areas (p = 0.008). In the second observed period, TB was significantly more associated with chronic obstructive pulmonary disease (p = 0.001) and comorbidities with TB were significantly more frequent (p = 0.006). During the 2000–2002 period, there were more severe clinical forms, with severe radiological changes, bilateral parenchymal and cavernous forms (p = 0.08). Mild unilateral parenchymal lesions were more common in the last 3 years (p = 0.02). Conclusion. Social determinants, older age and comorbidities are the most important risk factors for the persistent number of patients, and therefore this target group needs attention during active approach in TB screening.
Keywords: tuberculosis; sociological factors; demography; risk factors; morbidity.